Comparing Clinical and Radiological Outcomes of Volar Plating with Alternative Treatments for Distal Radius Fractures - Dr. R.Aswin Sundar; Dr. Yeshwanth Subash (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Fractures at the distal end of the radius pose a significant issue in orthopedic practice, representing a substantial proportion of upper extremity fractures. The functional results of these fractures may be impacted by problems like carpal instability, diminished grip strength, and malunion. The current research aims to evaluate the anatomical and functional outcomes of open reduction and plate fixation for distal radius fractures(Distal Radius Fractures) and compare them with alternative treatments, considering the potential for improved outcomes with volar plating. Materials and Methods:Prospective research was done at Saveetha Medical College and Hospital from June 2022 to September 2023, involving 30 patients with distal radius fractures. Patients aged 18 years and above with unilateral extra-articular fractures were included. Treatment options included volar plating, cast application, and external fixation with K-wires. Functional outcomes have been evaluated with Demerit score by Gartland and Werley at regular follow-up intervals. Results: The study comprised 30 patients, with a mean age of 42.6 years, predominantly males. Radiographic assessment based on the AO classification system revealed various fracture types. Volar plating demonstrated superior restoration of radial inclination, radial length, as well as volar angle compared to other treatments. As per the Gartland and Werley criteria, functional outcomes were significantly better in thevolar plating group. Complications like wrist pain, irregular articular surface, and finger stiffness were found across treatment modalities. Conclusion:Volar plating emerges as a superior treatment option fordistal radius fractures, offering better anatomical and functional outcomes compared to cast immobilization and external fixation. Early primary fixation with volar locking plates facilitates rapid return to regular activities and prevents complications associated with long-term fixation. This study confirms the efficacy and superiority of volar plating in managing distal radius fractures, particularly in preserving reduction and preventing complications across various fracture types and patient demographics.